Contribution to solution of pressure losses of heat exchanger - Paulinyová, Blanka; Zvarková, Daniela; Mikulík, Marián (Communications - Scientific letters of the University of Zilina, 1999)
This paper tells deals withe the calculation of pressure losses of heat exchangers and its individual parts. Local and length pressure losses in circular sections and also sections of different shape are dealt with. There are different alternatives of tubular heat exchangers connection. Liquid and gaseous heat carrying agents and various coolants can be used. It is possible to dimension pumps or ventilators by this calculation. Operation and investing charges also depend on that.